Impact of VAT on UAE Economy - Zafarullah, Muhammad (Asian Development Policy Review, 2018)
The local people and the immigrants that lived in UAE have had enjoyed the free tax system of the kingdom for years now and now a sudden change to this system is bound to have an impact not only on the economy, but on way business has been done before and now. The reason for the UAE to decide to implement the tax system in their kingdom is due to dropping oil prices around the world, which is decreasing the kingdom’s revenue and to stabilize this revenue the government has decided to implement tax system. The United Arabs Emirates announcement in 2011 which was to embark on a process of developing a VAT which was proposed to be 5% rating which was going to be implemented in 2014 or by 2015. The ministry of finance finalizes a report on the study of social and economic effects of the same VAT which would have on the nation upon fully implementation which was approximated to take 3 years from a point which the all general principles and laws were agreed upon all member countries of the union of GCC. Though the implementation of VAT is more likely to provide the government with the necessary revenue their need to maintain the functionalities, but at the same time it is going to raise up several challenges, such as tax fraud. Since, business is going to have an extra expenditure and to get rid of this extra expenditure it is very likely that the business organization can resort to tax fraud as seen in many other countries. This tax fraud is a grave issue to any government as it increases corruption in a country. Hence, the government needs to increase its vigil so that it can keep this threat under control and ensure the liability of tax.